1998
DOI: 10.4269/ajtmh.1998.58.638
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of artemether/benflumetol, a new antimalarial and pyrimethamine/sulfadoxine in the treatment of uncomplicated falciparum malaria in African children.

Abstract: We report here the results of a randomized double blind trial comparing coartemether (CGP56697), a combination of artemether and benflumetol, with pyrimethamine/sulfadoxine (P/S). Two hundred eighty-seven children 1-5 years of age with uncomplicated falciparum malaria were enrolled at two centers in The Gambia between July 1996 and December 1996. Following treatment, children were visited at home every 24 hr until a blood film free of asexual parasites was obtained. Genotyping of parasites was used to distingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
58
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 18 publications
12
58
0
1
Order By: Relevance
“…Furthermore, for isolates where both new and recrudescent genotypes are present, there is no agreed standard on whether such mixed infections should be classified as new, recrudescent, or undetermined genotypes. Some studies have excluded them from analysis (31,211), while others have classified them as either reinfections or recrudescence (103,172,215). A recent study in Uganda has suggested that classifying such infections as new is the most accurate option (38).…”
Section: Methods For Monitoring Parasite Resistancementioning
confidence: 99%
“…Furthermore, for isolates where both new and recrudescent genotypes are present, there is no agreed standard on whether such mixed infections should be classified as new, recrudescent, or undetermined genotypes. Some studies have excluded them from analysis (31,211), while others have classified them as either reinfections or recrudescence (103,172,215). A recent study in Uganda has suggested that classifying such infections as new is the most accurate option (38).…”
Section: Methods For Monitoring Parasite Resistancementioning
confidence: 99%
“…However, children in the CQ-AS treatment group frequently became gametocyte positive in the third and fourth weeks after treatment and carried gametocytes at relatively high densities (2), which shows that this particular combination would not provide a sustainable long-term benefit in reducing the spread of drug-resistant parasites. Other AS combinations tested with the same population, such as sulfadoxinepyrimethamine plus AS or co-artemether (10,11), give more sustained reductions in the levels of gametocyte carriage, as the level of resistance to the accompanying drug(s) remains low.…”
Section: Vol 48 2004 Antimalarial Combination Therapy and Transmissmentioning
confidence: 99%
“…The most widely adopted of these combinations in sub-Saharan Africa is artemether-lumefantrine (AL) (32). The recent emergence of resistance to artemisinin on the Thai-Cambodian border (23,5) establishes an urgent need for validated molecular markers of resistance to ACT in general and to AL in particular.…”
mentioning
confidence: 99%